Determinación del porcentaje óptimo de sustitución de harina de trigo por harina de amaranto en la elaboración de galletas: Determination of the optimal percentage of substitute for wheat flour with amaranth flour in the preparation of cookies (La U Investiga, 2019)
The research work consisted of determining the optimal percentage of substitution of wheat flour for amaranth flour for the production of biscuits. The methodology used was an experimental design (DCL Latin Square Design) in which we worked with mixtures of wheat flour and amaranth in proportions of T1 75:25, T2 50:50, T3 25:75 and T4 100: 0 respectively. The variables evaluated were sensory analysis, pH, protein andhumidity. The biscuit formulations were subjected to a process under equal conditions of preparation, cooking and evaluation. As a result, all treatments had statistically significant differences with an error of 5%. The samples had a pH between 6.14 and 6.33, being within the requirements of the NTE INEN 2 085: 2005 standard: Cookies. Requirements The amaranth flour contributed to improve the nutritional quality of thecookies, raising the protein content of the cookies. The flavor profile of all the samples was performed, finding that the best was T2. It was determined that the optimal percentage of substitution of wheat flour for amaranth flour was T2 50:50, because it presents better sensory and nutritional characteristics.
Keywords: cookies; amaranth; flour; nutrition; protein